Persistence of Timothy in Mixture with Smooth Meadow Grass - Björnsson, H. (UKnowledge, 2023)
Timothy (Phleum pratense) is the most common grass species in Iceland for the production of high quality herbage for dairy cows. For this purpose timothy is cut early, often around heading. The high quality, however, is at the cost of limited persistence of timothy. If cut late, three to four weeks after heading, timothy cultivars of northern origin can sometimes dominate for a long time, especially if the aftermath is not cut or grazed. Earlier experiments have shown that, relative to a late cutting treatment, the percentage timothy in the first harvest is reduced by one unit for each week that the harvest is moved forward (Helgadóttir & Hermannsson, 1991). This effect is cumulative over the years and the result applies to swards where all of the fertiliser is applied in spring and smooth meadow grass (Poa pratensis) is present in the sward, either sown or invaded. Experiments were run to further study the persistence of timothy under different cutting treatments and N applications and the effect of cultivars of both timothy and smooth meadow grass.